IDENTIFIKASI VARIABEL RISIKO PADA PENINGKATAN JALAN BINALATUNG DI KOTA TARAKAN DARI PERSPEKTIF OWNER - Aidil, Rachmad; Prihartanto, Eko (Borneo Engineering : Jurnal Teknik Sipil, 2019)
Road improvements in the city of Tarakan are mostly carried out to support people's welfare. roads in coastal areas in general are far from good, this is seen from the difficulty of access. the coastal area of the city of Tarakan is very dependent on land transportation facilities to meet their daily needs. this research was taken from a road improvement project, so that risks will be observed from the point of view of the Public Works and Spatial Planning Service as the project owner. The methodology used is conducting questionnaires and interviews. respondents from this study were the Public Works and Spatial Planning Service. with the type of qualitative description research. The results obtained in this study were in the form of risk identification that occurred during the road improvement project on the binalatung road in Tarakan City which had 93 overall risk variables after the method of analyzing probability and statistical relevance obtained a risk event rank of 35 variables.